(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This study presents the results of a comprehensive investigation into the chemical composition of the essential oil extracted from the aerial parts of Lallemantia royleana (Benth.) Benth. The qualitative and quantitative analysis of the volatile constituents was performed using gas chromatography coupled with mass spectrometry (GC–MS). The plant material was collected during the active vegetative growth phase in May 2024 from the experimental plot of the Botanical Garden of the National University of Uzbekistan named after Mirzo Ulugbek (Tashkent city). A total of 70 volatile compounds were identified, forming the chemical profile of the essential oil. The major constituents of the oil were β-ocimene (15.67%), citral (12.59%), nerol (12.72%), and β-citral (9.15%). These compounds exhibit significant biological activities, including antimicrobial, antioxidant, and anti-inflammatory effects, which support the potential of L. royleana as a valuable source of natural bioactive substances. The high content of monoterpenes and aldehydes in the essential oil highlights its aromatic and therapeutic properties, opening up broad prospects for its use in the pharmaceutical, food, cosmetic, and perfume industries. The findings confirm the significant potential of L. royleana as medicinal and technical raw material and emphasize the need for further research focused on standardization, biological evaluation, and industrial application of its essential oil.